Myalgia Association with Atorvastatin, Rosuvastatin and Simvastatin (Medical Forum Monthly, 2024)
Objective: To determine the myalgia association with atorvastatin, rosuvastatin and simvastatinStudy Design: Descriptive studyPlace and Duration of Study: This study was conducted at the cardiac ward, civil hospital from March 2013 to August 2013Materials and Methods: This study was done by taking the feedback of patients on a questionnaire set in conciliation of objectives. Data collection was done for six months. Myalgia was confirmed clinically via many questions asked directly to patients and its intensity through visual analog scale. Results: Study involved 300 patients between age 25-70 years and mean age was 55.7yrs ±7.575. Male patients were 218(72.67%) whereas females were 82(27.33%). Myalgia prevalence was categorize according to the type of statin as 10% in atorvastatin group, 11.34% in Rosuvastatin group and 16% was found in patients those were under treatment of simvastatin. In the atorvastatin group myalgia was found positively correlated with dose of atorvastatin as well as 5% cases were found with dose of 40mg. in the Rosuvastatin group majority of the cases 5.34% were found with 20mg, while in simvastatin group 8% cases were found with 10mg simvastatin. According to the VAS, 5% case was found with mild myalgia and 6.66% were noted with moderate myalgia while severe condition was not found in any case.6% cases were found with moderate myalgia out of 133 cases in Rosuvastatin group, 8% cases were noted with moderate myalgia out of 50 cases in simvastatin group, while only 3% patients were found with moderate myalgia in atorvastatin group out of 100 cases.Conclusion: Simvastatin is highly associated with myalgia as compare to others but not significant. Rosuvastatin, Atorvastatin and Simvastatin are positively associated with severity of myalgia after increases the dose.